European Respiratory Society statement: diagnosis and treatment of pulmonary disease in α1-antitrypsin deficiency. Issue 5 (30th November 2017) - Miravitlles, Marc; Dirksen, Asger; Ferrarotti, Ilaria; Koblizek, Vladimir; Lange, Peter; Mahadeva, Ravi; McElvaney, Noel G.; Parr, David; Piitulainen, Eeva; Roche, Nicolas; Stolk, Jan; Thabut, Gabriel; et al.
Α1 -antitrypsin deficiency (AATD) is the most common hereditary disorder in adults. It is associated with an increased risk of developing pulmonary emphysema and liver disease. The pulmonary emphysema in AATD is strongly linked to smoking, but even a proportion of never-smokers develop progressive lung disease. A large proportion of individuals affected remain undiagnosed and therefore without access to appropriate care and treatment. The most recent international statement on AATD was published by the American Thoracic Society and the European Respiratory Society in 2003. Since then there has been a continuous development of novel, more accurate and less expensive genetic diagnostic methods. Furthermore, new outcome parameters have been developed and validated for use in clinical trials and a new series of observational and randomised clinical trials have provided more evidence concerning the efficacy and safety of augmentation therapy, the only specific treatment available for the pulmonary disease associated with AATD. As AATD is a rare disease, it is crucial to organise national and international registries and collect information prospectively about the natural history of the disease. Management of AATD patients must be supervised by national or regional expert centres and inequalities in access to therapies across Europe should be addressed. Description of the best practice in diagnosis and treatment of pulmonary disease in alpha-1 antitrypsin deficiency http://ow.ly/fD3S30fuy4H